Determining Curie temperatures in dilute ferromagnetic semiconductors: high Curie temperature (Ga,Mn)As - Wang, M.; Marshall, R.A.; Edmonds, K.W.; Rushforth, A.W.; Campion, R.P.; Gallagher, B.L. (American Institute of Physics, 2014)
In this paper, we use simultaneous magnetometry and electrical transport measurements to critically examine ways in which the Curie temperature (TC) values have been determined in studies of dilute magnetic semiconductors. We show that, in sufficiently homogeneous samples, TC can be accurately determined from remanent magnetization and magnetic susceptibility and from the positions of the peak in the temperature derivative of the resistivity. We also show that the peak of the resistivity does not occur at TC, as illustrated by a (Ga,Mn)As sample for which the peak of the resistivity is at 21361K when TC is only 17861K